IMPLEMENTASI KEBIJAKAN PENGANGKATAN TENAGA HONORER MENJADI CALON PEGAWAI NEGERI SIPIL DI KANTOR BKD PROVINSI MALUKU UTARA - Wattimena, Meggi Fabiola (JURNAL ADMINISTRASI PUBLIK, 2014)
Abstract: Procurement ofCivil Serviceisa processof activitiesto fill the vacancy formation. In connection withthis, every Indonesian citizen who meets there quirements setout in government regulations has an         equal             opportunityto apply and be appointed as civil servants. But the objective cituations showed many honorary workers who have served for so long do not appointed as Civil servants . Based onthe matter, this study intend to answer the question of how the implementation of policy appointment of Honorary Workers to become candidates for Civil Servants. This study uses qualitative methods.This study using a sample taken at theoffice of the Regional Employment Agency North Maluku provinceby using the interview technique 7 questions to 15 respondents. Qualitative analysis consists of 3steps. First, word reductionis the selection process focusing on simplification and racial formations that emerge from therough notes written on the field. Second,presentation of data that coversdrawing conclusions and taking action and the third is Verification whereresearc her draws conclusions and verify the symptom so btained from   the field.  Apart from the 3 steps, the researcheris also supported by document so btained from the office of research. From these results we canconclude that the government remain objective in the assessment of each participantis concerned and in the recruitment of civil servants, govermant take into account the ability of the regional budget because it canresult in the ability to provide public services. Because if the budget mostly used to fund the salaries,thanthe public might suffered. Based on this conclusion, it is better that governmentor         government agency does not receive honorary instantly, because of the fact that most honorary workers who are working now are recruited without the selection but based only on kinshipand there for ethe government should hold a cleanselection for all contract officersin government agencies so that it will result a higher quality. Also, the government should postpone to receive honorary workes before resolving all problems in their respective areas. Keywords: recruitmen of honorary workes